Here is your question↑↑↑
Attachments:
![](https://hi-static.z-dn.net/files/dc4/ac2cd40a7a94d463f93383a616c606a8.jpg)
Answers
Answered by
14
1.
Therefore,
----(1)
Again,
Putting the value in equation (1) We will get,
2. As the same tension is acting in both the strings.
2T CosØ = mg
T = mg/2CosØ
3. Here first we will take the horizontal component of the body then we will take vertical component of the body.
----(1)
Again,
----(2)
Putting the value of in eq(2).
Solving this we will get,
Putting the value of in equation we get,
Attachments:
![](https://hi-static.z-dn.net/files/de5/774e65b4665025c6722a2213d217a5dd.jpg)
![](https://hi-static.z-dn.net/files/d6e/3f6658895990bec55fc42b09be39e0b8.jpg)
![](https://hi-static.z-dn.net/files/db0/61aba6296e0550540e140d46b2f3ddaf.jpg)
iamprachi65:
Awesome answer
Answered by
1
Answer:
1. {T}_{2}Sin{60}^{\circ} = {T}_{1}Sin{30}^{\circ}T
2
Sin60
∘
=T
1
Sin30
∘
\dfrac{\sqrt{3}{T}_{2}}{2} = \dfrac{{T}_{1}}{2}
2
3
T
2
=
2
T
1
Therefore,
{T}_{2} = \dfrac{{T}_{1}}{\sqrt{3}}T
2
=
3
T
1
----(1)
Again,
{T}_{1}Cos{30}^{\circ} + {T}_{2}Cos{60}^{\circ} = 200NT
1
Cos30
∘
+T
2
Cos60
∘
=200N
\dfrac{\sqrt{3}{T}_{1}}{2} + \dfrac{{T}_{1}}{2}\times\dfrac{1}{2} = 200
2
3
T
1
+
2
T
1
×
2
1
=200
\dfrac{6{T}_{1}+2{T}_{1}}{4\sqrt{3}}=200
4
3
6T
1
+2T
1
=200
\bf{T}_{1} = 100\sqrt{3}\:NT
1
=100
3
N
Putting the value in equation (1) We will get,
\bf{T}_{2} = 100\:NT
2
=100N
2. As the same tension is acting in both the strings.
2T CosØ = mg
T = mg/2CosØ
3. Here first we will take the horizontal component of the body then we will take vertical component of the body.
{T}_{1}Cos{45}^{\circ} = {T}_{2}Cos{30}^{\circ}T
1
Cos45
∘
=T
2
Cos30
∘
\dfrac{{T}_{1}}{\sqrt{2}} = \dfrac{\sqrt{3}{T}_{2}}{2}
2
T
1
=
2
3
T
2
{T}_{1} = \dfrac{\sqrt{3}{T}_{2}}{\sqrt{2}}T
1
=
2
3
T
2
----(1)
Again,
{T}_{1}Sin{45}^{\circ}+{T}_{2}Sin{30}^{\circ}=300\:NT
1
Sin45
∘
+T
2
Sin30
∘
=300N ----(2)
Putting the value of {T}_{1}T
1
in eq(2).
\dfrac{\sqrt{3}{T}_{2}}{\sqrt{2}} \times \dfrac{1}{\sqrt{2}} + \dfrac{{T}_{2}}{2} \: = 300
2
3
T
2
×
2
1
+
2
T
2
=300
Solving this we will get,
\bf{T}_{2} = 300(\sqrt{3}-1)T
2
=300(
3
−1)
\bf{T}_{2} = 215.2 NT
2
=215.2N
Putting the value of {T}_{2}T
2
in equation we get,
{T}_{1} = \dfrac{\sqrt{3}}{\sqrt{2}} \times 300(\sqrt{3}-1)T
1
=
2
3
×300(
3
−1)
\bf{T}_{1} = 263.5\:NT
1
=263.5N
Hope the answer is help ful for you
Please brainlest me the answer
Attachments:
![](https://hi-static.z-dn.net/files/dc2/515cb79b59c1a220ba4dd4d16914c9c7.jpg)
![](https://hi-static.z-dn.net/files/d74/9097199c1aa5a4f0ac518e28b7c48648.jpg)
![](https://hi-static.z-dn.net/files/d38/fdd3538bd63d38bcacfeb85962beca3e.jpg)
Similar questions
Computer Science,
4 months ago
Science,
4 months ago
Economy,
8 months ago
Hindi,
8 months ago
Science,
1 year ago